All‐Fiber Dual‐Wavelength Thulium–Bismuth Codoped Fiber Laser. Issue 10 (26th July 2013) - Saidin, N.; Zen, D. I. M.; Damanhuri, S. S. A.; Harun, S. W.; Ahmad, H.; Dimyati, K.; Halder, A.; Paul, M. C.; Pal, M.; Bhadra, S. K.
ABSTRACT We report a room temperature all‐fiber dual‐wavelength Thulium–Bismuth codoped fiber laser operating in 1900 nm region using a single fiber Bragg grating (FBG) in a ring configuration. The addition of Bismuth ions as codopant in the gain medium enhances the inhomogeneous broadening effect in the fiber and thus allows a dual‐wavelength oscillation with the assistance of the FBG that has a flat top reflection spectrum. By pumping the gain medium with 1552 nm laser, a dual‐wavelength output lines are obtained at 1901.09 and 1901.98 nm with a spacing of 0.89 nm and an optical signal to noise ratio of more than 45 dB as the polarization controller (PC) orientation is adjusted to balance the loss between the two wavelengths. The dual‐wavelength laser can also be switched to operate in single‐wavelength at either 1901.07 or 1901.98 nm by altering the intracavity polarization using the PC. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2324–2326, 2013